Application of Micro Educational Management in Documenting the Knowledge of Biology Teachers in Baghdad Schools - Allawi Alsaadi, Fadhil Kadhim; Khalkhali, Ali; Abed Ahmed, Salwan; Aghakasheri, Zohreh (Assessment and Practice in Educational Sciences, 2026)
This study aimed to design a localized model for documenting the knowledge of biology teachers in Baghdad secondary schools, based on the principles of micro educational management. Micro educational management conceptualizes the teacher as a leader at the classroom level who manages the teaching and learning process through moment-to-moment decision-making and continuous reflection. Within this framework, a teacher’s professional knowledge is categorized into three types: “substantive knowledge” (scientific concepts), “contextual knowledge” (lived experience), and “explicit knowledge” (observable documentation). This qualitative study was conducted within an interpretive paradigm, employing semi-structured interviews, participatory observation, and document analysis of 12 biology teachers in four schools in Baghdad. The data were analyzed using the Attride-Stirling thematic analysis method. Findings led to the extraction of five basic themes: documentable content as substantive knowledge, strategies for recording and organizing knowledge, implicit and non-recordable knowledge, criteria for selecting documentable content, and enablers and barriers to documentation. These themes were ultimately integrated into an overarching theme entitled “The Intelligent Model of Teacher Knowledge Documentation within the Framework of Micro Educational Management.” This model demonstrates that documentation becomes intelligent and effective when the teacher, guided by reflective and situational rationality, assumes the role of a knowledge manager and designer, establishing interconnections among the three types of knowledge. This process transforms documentation from a mere administrative task into a research-based and knowledge-creating practice that leads to sustainable individual and organizational learning. The results indicate that implementing this model can foster teachers’ professional growth, strengthen the school’s intellectual capital, and enhance the quality of biology instruction. The study underscores the necessity of institutionalizing documentation within the school culture and providing institutional support for teachers to realize micro educational management.